A provisional strategy for treating true bifurcation lesions employing a scoring balloon for the side branch. Issue 3 (9th March 2013) - Weisz, Giora; Metzger, D. Christopher; Liberman, Henry A.; O'Shaughnessy, Charles D.; Douglas, John S.; Turco, Mark A.; Mehran, Roxana; Gershony, Gary; Leon, Martin B.; Moses, Jeffrey W.
<x xml:space="preserve">Abstract</x> Background The provisional approach for bifurcation stenting with side‐branch balloon angioplasty is associated with dissections and suboptimal results requiring kissing balloon techniques or bailout stenting. We hypothesized that using a scoring balloon for the side branch and a drug‐eluting stent for the main vessel might improve outcomes of true bifurcation lesions. Methods and Results A total of 93 patients with complex bifurcations were enrolled in a multicenter, single‐arm, prospective clinical trial. A drug‐eluting stent was deployed in the main vessel following dilatation of the side‐branch stenosis with a scoring balloon. The overall angiographic success rate was 93.5%, and procedural success rate was 91.4%. The final diameter stenosis was 13.9% ± 7.2% for the main vessel and 33.3% ± 22.9% for the side branch. Crossover to stent deployment in the side branch was required in 10.8%. The postscoring balloon dissection rate was 8.2% and 6% (all ≤ class C) for the main vessel and side branch respectively, which was reduced to 1.1 and 2.1% poststenting. At 9‐month follow‐up, the composite MACE rate [cardiac death, myocardial infarction, or target lesion revascularization (TLR)] was 5.4%, including a TLR rate of 3.3% (1.1% from hospital discharge to 9 months). Conclusion The 9‐month results of the AGILITY trial support a simple provisional strategy for treating complex true bifurcation lesions with deployment of a drug‐eluting stent in the main vessel after dilatation of the side‐branch vessel with a scoring balloon. This strategy was associated with excellent and safe procedural results, a low rate of crossover to side‐branch stenting, and favorable outcomes. © 2013 Wiley Periodicals, Inc.